Comparison of the osteogenic effectiveness of an autogenous demineralised dentin matrix and Bio-Oss® in bone augmentation: a systematic review and meta-analysis. Issue 7 (September 2022) - Li, Yanfei; Zhou, Wanhang; Li, Peiyi; Luo, Qipei; Li, Anqi; Zhang, Xinchun
Abstract: This study aimed to evaluate the clinical efficacy and histological outcomes of autogenous demineralised dentin matrix (ADDM) as bone graft material compared with Bio-Oss® in bone augmentation for the treatment of patients with oral bone deficits. Eight databases (PubMed, EMBASE, Cochrane Library, Science Direct, Scopus, Web of Science, CNKI, and WFPD) were searched for randomised controlled trials (RCT) performed from the date of inception of each database to July 2021. The Cochrane Collaboration's risk assessment tool was used to conduct the methodological quality assessment. Stata 15.0 software was used to perform data analysis. Seven RCTs including 220 patients were considered eligible for this study. No significant difference was found in the percentage of new bone formation (NBF) and implant stability quotient (ISQ). Patients who received ADDM grafting showed a significantly lower sinus height (SH) and percentage of residual graft material (RGM) compared with Bio-Oss® grafting. ADDM is as effective as Bio-Oss® in bone augmentation for oral bone defects.